2009
DOI: 10.1152/ajpregu.00252.2009
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diets induce a rapid loss of the insulin anorectic response in the amygdala

Abstract: (FI). The central bed nucleus of the amygdala (CeA), as other regions of the brain regulating feeding behavior, expresses insulin receptors. Our objectives were to show an insulin anorectic response in the amygdala, study the effect of high-fat diets on this response, and map the neural network activated by CeA insulin using c-Fos immunohistochemistry. Sprague-Dawley (SD) rats fitted with unilateral CeA cannulas were adapted to a low-fat (LFD) diet before they were fed a high-fat diet (HFD). Their feeding resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
39
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 57 publications
10
39
0
3
Order By: Relevance
“…At that time, we speculated that fatty acids derived from visceral fat depots may cause insulin resistance of the brain and therefore lead to further weight gain. Indeed, recent studies confirmed that intracerebroventricular palmitic acid infusion and high-fat diet induce insulin resistance in different brain regions in mice and rats [12,14,15]. These observations, together with the present finding of high insulin sensitivity in the brain associated with lower intake of saturated fat, may suggest that insulin resistance in the brain elevates serum concentrations of saturated fatty acids not only by increasing visceral fat mass, but also more directly by decreasing physical activity and increasing intake of saturated fat.…”
Section: Discussionsupporting
confidence: 83%
“…At that time, we speculated that fatty acids derived from visceral fat depots may cause insulin resistance of the brain and therefore lead to further weight gain. Indeed, recent studies confirmed that intracerebroventricular palmitic acid infusion and high-fat diet induce insulin resistance in different brain regions in mice and rats [12,14,15]. These observations, together with the present finding of high insulin sensitivity in the brain associated with lower intake of saturated fat, may suggest that insulin resistance in the brain elevates serum concentrations of saturated fatty acids not only by increasing visceral fat mass, but also more directly by decreasing physical activity and increasing intake of saturated fat.…”
Section: Discussionsupporting
confidence: 83%
“…The CeA, indeed, plays a key role in the non-homeostatic regulation of feeding and the regulation of macronutrient selection (King et al, 1998;Will et al, 2004). Rats with ablation of the CeA display a reduction in body weight as well as lower preferences for tasty solutions (Touzani et al, 1997), and the activation/inhibition of specific neuropeptide/hormone receptors or cell types within the CeA has been shown to modulate food intake, especially if palatable (Boghossian et al, 2009;Primeaux et al, 2006). The CeA has also recently been implicated in excessive eating .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, insulin receptor knockdown in the catecholaminergic neurons of the ventral tegmental area increases body weight and fat mass in mice (14), whereas direct injection of insulin into the central bed nucleus of the amygdala decreases food intake in healthy but not high fat-fed rodents (15). Insulin responsiveness in the dorsal vagal complex (DVC) and the subsequent control on glucose homeostasis have also been examined (16).…”
mentioning
confidence: 99%